Cyclic dipeptides from endophytic bacterium Bacillus velezensis as potential flavor precursors - Li, Tianxiao; Fang, Yaning; Chai, Zhishun; Ji, Lingbo; Jiang, Zhongrong; Meng, Dandan; He, Baojiang; Hu, Xiaolong; Xi, Hui; Jia, Xuewei; Li, Dongliang (Frontiers in Microbiology, 2025)
Cyclic dipeptides represent a class of intriguing molecules with a wide range of biological activities, but their potential application as flavor precursors has not been previously reported. In this study, a flavor-producing bacterium Bacillus velezensis was screened out from 35 isolated endophytic bacteria. Gas chromatography-mass spectrometry (GC-MS) analysis suggested that the fermentation broth of B. velezensis contained flavor compounds and high amount of cyclic dipeptide flavor precursors. Three cyclic dipeptide flavor precursors, namely cyclo (L-prolyl-L-valine) (1), cyclo (L-prolyl-L-isoleucine) (2), and cyclo (L-prolyl-L-leucine) (3), were further isolated from the fermentation broth extraction through Sephadex LH-20 column chromatography and semi-preparative high-performance liquid chromatography (HPLC), and were identified by nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS). Flavor precursors can generate aroma components during pyrolysis, and the pyrolysis of compounds 1 and 3 were performed using pyrolysis GC-MS (Py-GC-MS) to analyze the flavor products. According to the relative odor activity value (ROAV) analysis, the key pyrolysis flavor compounds were revealed as 6-heptyl-5,6-dihydro-2H-pyran-2-one, isobutyric acid, 4-methyl-2-oxo-pentanoic acid ester, pyrrole derivatives, and pyrazine derivatives, which could give great contributions to milky, roasting, fruity, sweetness, and nutty aromas. The pyrolysis formation pathway of these flavor compounds was also proposed in detail. Addition of fermentation broth from the flavor-producing bacteria on cigar tobacco leaves significantly enhanced the milky, roasting, fruity, sweetness, and nutty aromas, which further demonstrated the flavor enhancing ability of cyclic dipeptides. This is the first report of flavor enhancing effects of cyclic dipeptides utilized as flavor precursors.